Adaptive Metabolism in Staphylococci: Survival and Persistence in Environmental and Clinical Settings. (20th September 2018) - Onyango, Laura A.; Alreshidi, Mousa M.
Abstract : Staphylococci are highly successful at colonizing a variety of dynamic environments, both nonpathogenic and those of clinical importance, and comprise the list of pathogens of global public health significance. Their remarkable survival and persistence can be attributed to a host of strategies, one of which is metabolic versatility—their ability to rapidly alter their metabolism in the presence of transient or long-term bacteriostatic and bactericidal conditions and facilitate cellular homeostasis. These attributes contribute to their widespread dissemination and challenging eradication particularly from clinical settings. The study of microbial behaviour at the metabolite level provides insight into mechanisms of survival and persistence under defined environmental and clinical conditions. This paper reviews the range of metabolic modulations that facilitate staphylococcal acclimatization and persistence in varying terrestrial and host conditions, and their public health ramifications in these settings.